Up-to-date overview of imaging techniques in the diagnosis and management of inflammatory bowel diseases - Katarzyna B. Biernacka; Dobromiła Barańska; Piotr Grzelak; Elżbieta Czkwianianc; Katarzyna Szabelska-Zakrzewska (Gastroenterology Review)
Radiological examination occupies a significant role, complementary to endoscopic studies, in the diagnostic process of inflammatory bowel disease (IBD). Both ulcerative colitis and Crohn’s disease, due to multiple remissions and relapses, require repetitive examinations to evaluate the disease extent, severity, and response to pharmacological treatment. Whereas the use of barium contrast studies is progressively reduced, plain radiography confirms its utility as a first-line imaging tool for acute abdomen. Computed tomography remains an easily accessible and effective method to demonstrate disease activity and extraintestinal manifestations. However, the related radiation exposure reduces its applicability to urgent situations. Ultrasound and magnetic resonance, with the great advantage of avoiding ionising radiation, are highly recommended to present the complications of IBD. Use of oral and intravenous contrast in computed tomography enterography and magnetic resonance enterography demonstrates IBD involvement in the small intestine wall, which is difficult to assess in other radiological and endoscopic examinations.